THE INFLUENCE OF TAXPAYER AWARENESS, TAX SANCTIONS, TAXPAYER KNOWLEDGE AND PUBLIC SERVICE ACCOUNTABILITY ON LAND AND BUILDING TAXPAYER COMPLIANCE IN MEDAN CITY AREA - Nadya Safitri Br Sembiring; Yois Nelsari Malau; Balqis Gelcya; M. Hafiz Kurniawan; Wenny Anggeresia ginting (Journal Accounting International Mount Hope, 2024)
Good public service accountability, sufficient knowledge, and high taxpayer awareness can all promote compliance with land and building taxes. Furthermore, enforcing stringent tax penalties is crucial in boosting this kind of compliance. This study's objective is to examine how compliance of taxpayers with land and construction taxes in Medan City is impacted by awareness of taxpayers, tax penalties, taxpayer knowledge, and public service accountability. Multiple linear regression analysis with 100 samples is the technique employed. The findings demonstrate that taxpayer compliance is significantly improved by awareness and public service accountability. Tax penalties have also been shown to play a role, and taxpayer awareness has a big impact. Simultaneously, Medan City taxpayer compliance with land and construction taxes is significantly impacted by Awareness of taxpayers, taxpayer knowledge, public service accountability, and tax penalties. Building and land taxes compliance in Medan City is significantly impacted by taxpayer awareness, tax penalties, taxpayer awareness and accountability for public service. According to the study's findings, these elements work together to raise tax compliance in the area.